microRNA in Cardiovascular Aging and Age-Related Cardiovascular Diseases - de Lucia, Claudio; Komici, Klara; Borghetti, Giulia; Femminella, Grazia Daniela; Bencivenga, Leonardo; Cannavo, Alessandro; Corbi, Graziamaria; Ferrara, Nicola; Houser, Steven R.; Koch, Walter J.; Rengo, Giuseppe (Frontiers in Medicine, 2017)
Over the last decades, life expectancy has significantly increased although several chronic diseases persist in the population, with aging as the leading risk factor. Despite improvements in diagnosis and treatment, many elderlies suffer from cardiovascular problems that are much more frequent in an older, more fragile organism. In the long-term, age-related cardiovascular diseases (CVDs) contribute to the decline of quality of life and ability to perform normal activities of daily living. Micro-RNAs (miRNAs) are a class of small noncoding RNAs that regulate gene expression at the post-transcriptional level in both physiological and pathological conditions. In this review we will focus on the role of miRNAs in aging and aged-related CVDs as heart failure, hypertension, atherosclerosis, atrial fibrillation and diabetes mellitus. MiRNAs are key regulators of complex biological mechanisms, representing an exciting potential therapeutic target in CVDs. Moreover, one major challenge in geriatric medicine is to find reliable biomarkers for diagnosis, prognosis and prediction of the response to specific drugs. MiRNAs represent a very promising tool due to their stability in the circulation and unique signature in CVDs. However, further studies are needed to investigate their translational potential in the real clinical practice.